A rare case of a natural contact zone in Morocco between an autopolyploid and an allopolyploid of Centaurea aspera with sterile tetraploid hybrids. (2nd January 2015) - Garmendia, A.; Ferriol, M.; Juarez, J.; Zając, A.; Kałużny, K.; Merle, H.; Peeters, T.
Abstract A new contact zone between Centaurea aspera and Centaurea seridis was found in Morocco. Chromosome counts and flow cytometry showed that both taxa were tetraploid (4x = 44). A literature review and morphometric analysis established that C. aspera corresponds to the autopolyploid C. aspera subsp. gentilii and C. seridis corresponds to the allopolyploid C. seridis var. auriculata. This contact area was compared with the homologous contact zones in Spain formed by the diploid C. aspera subsp. stenophylla and the tetraploid C. seridis subsp. maritima. Natural hybrids between parental species were frequent in both areas. In Spain, hybrids were triploid (from reduced gametes A and gamete AB), highly sterile and exerted a 'triploid block'. In Morocco, cytometry showed that hybrids were tetraploid and, therefore, probably fertile, but all the capitula lacked achenes. It is likely that the resulting genome of the new tetraploid hybrid (AAAB), through the fusion of reduced gametes AA (from subsp. gentilii) and AB (from var. auriculata), could explain irregularities in meiosis through formation of aneuploid gametes and, therefore, infertility of the hybrid. Moroccan sterile tetraploid hybrids develop, but have the identical irregularities to Spanish triploids, probably due to the odd number of homologous chromosomes. The new hybrid is first described as C. x subdecurrens nothosubsp. paucispinus. In addition, distribution and ecological traits are analysed.